Comparative study of the antimicrobial activity between raw and powdered spices - Roza, Tasmia Azam; Amin, Sumaiya; Samanzar, Masaba; Annoor, Kazi Tanha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.